A Brief Review of Resseliella citrifrugis (Diptera: Cecidomyiidae), a Lesser-Known Destructive Citrus Fruit Pest. Issue 1 (12th October 2021) - Xia, Yulu; Ouyang, Ge-Cheng; Takeuchi, Yu
Abstract: The gall midge, Resselielia citrifrugis Jiang (Diptera: Cecidomyiidae), is a major citrus pest in China. The pest occurs widely in regions with tropical, subtropical, and temperate climates. Larvae feed inside the fruit, leading to premature fruit drop or damaged fruits. An infested fruit can have hundreds of larvae in it. The extent of losses varies, usually between 10 and 100%, depending on the grove management level. Resselielia citrifrugis hosts include common citrus varieties. China has no area-wide management program against the pest. Field pest management measures include grove sanitation, fruit bagging, and pesticide applications. This review identifies three scientific and technological gaps that need to be filled to protect the U.S. citrus industry from this pest. First, the taxonomical and systematic status of R. citrifrugis needs to be clarified and validated before the pest can be effectively regulated. Second, traps and/or lures for early detection of the pest need to be developed before the pest arrival. Third, pest risk mitigation measures against the pest need to be evaluated and strengthened.